2010
DOI: 10.1021/tx100125t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinically Used and Experimental Iron Chelators for Protection against Oxidative Stress-Induced Cellular Injury

Abstract: Iron imbalance plays an important role in oxidative stress associated with numerous pathological conditions. Therefore, iron chelation may be an effective therapeutic approach, but progress in this area is hindered by the lack of effective ligands. Also, the potential favorable effects of chelators against oxidative injury have to be balanced against their own toxicity due to iron depletion and the ability to generate redox-active iron complexes. In this study, we compared selected iron chelators (both drugs u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 59 publications
7
69
0
Order By: Relevance
“…For these latter ligands, this effect could lead to tumor cytotoxicity due to the redox activity of these complexes (Whitnall et al, 2006;Yu et al, 2011a). However, this could not explain the antitumor efficacy of deferasirox, as its iron complex is not redox-active (Bendová et al, 2010;Ha sková et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For these latter ligands, this effect could lead to tumor cytotoxicity due to the redox activity of these complexes (Whitnall et al, 2006;Yu et al, 2011a). However, this could not explain the antitumor efficacy of deferasirox, as its iron complex is not redox-active (Bendová et al, 2010;Ha sková et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we chose to administer deferasirox, a relatively new iron chelator that can be administered orally at once, has a good bioavailability of approximately 70%, with peak plasma levels between 2 and 4 h after ingestion, 27 and has been shown to protect against oxidative stress-induced damage in patients. [28][29][30][31] We chose a relatively high dosage of 30 mg/kg. 32 Although deferasirox has roughly the same characteristics as deferrioxamin with regard to the chelation of iron, there might be a difference in anti-oxidative capacity between the two compounds.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%
“…L1 protected neurons as well as fibroblasts against H 2 O 2 -induced cell death in vitro (165,189). It also protected an H9c2 cardiomyoblastderived cell line against model oxidative injury induced by tert-butyl hydroperoxide (15) and rat hearts against the ischemia-reperfusion injury (276). Two in vitro studies demonstrated that treatment with L1 resulted in an inhibition of DOX (0.6-1.8 lM) toxicity in both iron-loaded and normal cardiac culture cells (10,166).…”
mentioning
confidence: 98%
“…Furthermore, a short plasma halflife of DFO may also reduce its potential. In fact, numerous previous studies have demonstrated that DFO is clearly inferior in protecting cardiac cells from oxidative stressinducing agents as compared to smaller and more lipophilic ligands (15,93,188,238), and therefore during the last years, the research interest shifted in this direction.…”
mentioning
confidence: 99%
See 1 more Smart Citation